Edukasi Manfaat Tindak Lanjut Kolaboratif Hasil Supervisi Pendidikan Sebagai Strategi Pencapaian Standar Nasional Pendidikan - Fauzi, M. Asif Nur; Apip, Moch.; Warta, Waska (Universitas Islam Internasional Darullughah Wadda'wah, 2023)
Community Service (PKM) was initiated by the importance of education which is a pillar of sustainable national development. So quality education is an idea to produce superior output. So collaborative steps are needed to make this happen with follow-up educational supervision to achieve National Education Standards. This service is carried out using an awareness method through policy education given to service participants who are teachers, students and staff from SMA Kartika X-1 Jakarta. Based on the results of the education provided to community service participants at SMA Kartika If it is related to the educational follow-up activities that are implemented, namely the Management Review Plan (RTM) and Follow-up Plan (RTL). Meanwhile, if examined from the aspect of school reputation, this follow-up activity is oriented towards improving the positive image of the school through demonstrated academic quality